Received Experiences of Health Literacy Promotion for Blood Glucose Level Control and Body Weight Gain in Pregnant Women with Gestational Diabetes Mellitus: Atcharobon Sangprasert - Sosome, Boonsurb; Bootsri, Wilasinee; Sangprasert, Atcharobon; Punsomreung, Treechada; Howharn, Chularat; Kamdee, Bumpen; Suparasri, Porntipa; Pokathip, Supian; Yamanantakul, Prachayawatee; Rattanaprom, Panida; Turner, Kamolrat (Princess of Naradhiwas University Journal, 2024)
The purpose of this qualitative study was to examine how pregnant women with gestational diabetes mellitus experienced of health literacy promotion in controlling their blood glucose levels and weight gain. The ten hospitals involved in this study were five large general hospitals, one large community hospital, two community hospitals with over 120 beds, and two community hospitals with between 60 and 120 beds. 29 women with gestational diabetes mellitus served as primary informants, whereas nine registered nurses served as secondary informants. The research instruments were: 1) A general form for gathering data; 2) A semi-structured questionnaire for in-depth interviews was developed based on phenomenology and concepts related to health literacy promotion, which was tested with three pregnant women for easier understanding. The results demonstrated that every primary informant experienced anxiety and worry, which need to protect both the oneself and fetus. The experiences were divided into three categories: 1) First group could not recall all of their knowledge, did not search for more information, and were unable to apply what they did know; 2) Second group could recall suggestions and related numbers but were unable to adjust to the new diet; and 3) Third group could recall numbers, nutrition, and calorie calculations and independently seek out new information. The study's Recommendation that health care professionals should be sensitive while gathering for information regarding health literacy promotion to assist pregnant women with gestational diabetes mellitus control their blood glucose levels and gain weight faster than usual.